Anxious academics: talking back to the audit culture through collegial, critical and creative autoethnography. Issue 2 (15th March 2018) - Ruth, Damian; Wilson, Suze; Alakavuklar, Ozan; Dickson, Andrew
ABSTRACT: Our New Zealand university recently required us to produce portfolios for a research evaluation process. At a presentation promoting and explaining the process, we raised questions and objections. Pointlessly, it seemed. But we continued to rail and rant about it. One of us set in motion the following discussion, presented here as a series of critical and creative autoethnographic responses. We have resisted, with some anxiety, the urge and the expectation to theorize our experiences or to situate them within 'the literature'. Our proposition is that 'giving voice' in the manner in which we have done so is an affective means of 'talking back' against neo-liberal regimes of performativity which may also be effective as a form of localized resistance, strengthening our ability to cope with the anxiety such regimes provoke. We hope our efforts encourage others to develop critical, creative and collegial responses to academic audit regimes.